Tantangan dan Strategi Pengelolaan Diniyah Miftahul Hidayah: Analisis Kekurangan Infrastruktur, Tenaga Pengajar, dan Kendala Pembiayaan dalam Pelaksanaan KKN di Desa Tanjungrasa - Cecep Hidayat; Rena Fadilah Malik; Ade Ratno (Universitas Cokroaminoto Yogyakarta, 2026)
The Community Service Program (KKN) in Tanjungrasa Village faces various challenges in managing the Diniyah Miftahul Hidayah educational institution, particularly in terms of infrastructure, teaching staff, and funding. This study aims to analyze the existing issues and formulate strategies to enhance the effectiveness of managing the institution. A qualitative descriptive approach was employed using observation, interviews, and document studies as data collection techniques. The findings indicate that limitations in facilities and infrastructure, a shortage of qualified teaching staff, and insufficient operational funds are the primary obstacles in managing Diniyah Miftahul Hidayah. To address these issues, several strategies can be implemented, including strengthening collaboration with the government and private sector for infrastructure development, providing training programs for educators, and optimizing funding sources through community participation and donors. By implementing these strategies, it is expected that the sustainability and quality of education at Diniyah Miftahul Hidayah will improve significantly.